Auriculoterapia no tratamento do tabagismo na atenção primária de saúde - Gomes, Andréa de Oliveira Albuquerque Ferreira (2023)
Smoking is a chronic disease that affects public health and this study used auriculotherapy as a strategy to face the problem, a therapeutic technique of Traditional Chinese Medicine whose philosophy is the relationship of energy balance with the body and is inserted in the promotion in health of the Unified Health System. The study was carried out to assist in the Tobacco Control Program recommended by the SUS and aimed to assess the perceptions of smokers regarding the use of auriculotherapy to reduce smoking in primary health care. A qualitative descriptive study took place from May to August 2022 with eleven participants who were part of the smoking group offered by the Ministry of Health, who were interviewed and followed up for 10 weeks with the use of auriculotherapy, using mustard seeds . Data collection was carried out at the CDFAM Health Unit Prof: Gilmário Mourão Teixeira, in the city of Fortaleza-CE with eleven smokers enrolled in the Smoking Program. The effectiveness of the study results was evidenced by the reduction of symptoms related to smoking dependence, which was noticeable by all participants. The effectiveness of the study results was evidenced with the reduction of symptoms related to smoking dependence by all participants, there was smoking cessation by four participants, one of them without the interference of pharmacotherapy. It was found that socioeconomic and cultural factors interfered in the treatment of smoking reduction with the practice of auriculotherapy. At the end of the ten sessions, a reduction in anxiety, sadness, anger and stress was detected. There was a reduction in smoking in seven participants, considering through perceptions that socioeconomic factors interfered in the treatment. The practice of auriculotherapy contributed positively to the monitoring of smoking in primary care, in addition to the contribution of alcoholism cessation in two participants. This study considered ethical aspects of research involving human beings, which were strictly adopted in accordance with the resolution of the National Health Council - CNS, 466, of 2012. This research collaborated with the insertion of PICS in the SUS as a possibility of positively interfering in the quality of life of the participants who are part of the Health Unit.